Heartburn in children and adolescents in the presence of functional dyspepsia and/or irritable bowel syndrome correlates with the presence of sleep disturbances, anxiety, and depression. Issue 13 (2nd April 2021) - Colombo, Jennifer M.; Deacy, Amanda D.; Schurman, Jennifer V.; Friesen, Craig A.
Abstract : Abstract: The aim of this study was to assess the relationship of heartburn in pediatric patients with functional dyspepsia (FD) and irritable bowel syndrome (IBS) with gastrointestinal symptoms, sleep disturbances, and psychologic distress. The overlap in symptoms of FD, IBS, and gastroesophageal reflux disease (GERD) predicts greater symptom severity and decreased quality of life and presents opportunities for improved diagnostic classification and personalized therapeutics.A cross-sectional observational study of 260 pediatric patients with abdominal pain was conducted. Patients completed standardized questionnaires assessing clinical symptoms, sleep quality, and psychologic symptoms during routine clinical care. Questionnaire data were compared for patients reporting heartburn and not reporting heartburn using χ 2 and t tests where appropriate. Gastrointestinal symptoms were significantly more prevalent among patients with a positive report of heartburn (vs a negative report of heartburn): pain with eating (83% vs 67%, P  = .007), bloating (63% vs 44%, P  = .005), acid regurgitation (47% vs 24%, P  ⩽ .001), and chest pain (45% vs 20%, P  ⩽ .001). Likewise, initiating and maintaining sleep ( P  = .007), arousal/nightmares ( P  = .046), sleep-wake transition ( P  = .001), hyperhidrosis during sleep ( P  = .016), and anxiety ( P  = .001) and depression ( P  = .0018) were also significantly increased in patients who reported heartburn versus patients who did not report heartburn. Patients with a positive report of heartburn, whether classified as having FD and/or IBS, had increased gastrointestinal symptoms, sleep disturbances, anxiety, and depression than patients with a negative report of heartburn. A better understanding of these associations may allow for personalized treatment for youth with abdominal pain and heartburn as a primary symptom.